PRODUCTION OF CELLULASES AND XYLANASES BY SOME THERMOPHILIC FUNGI - S. M. REDDY, N. VENKATESHWARLU AND (Indian Phytopathology, 2002)
Production of cellulases (cellobiohydrolases, endoglucanase and ,a-glucosidase) and xylanase by four thermophilic fungi (Chrysosponum sulfureum, Penicillium purpurogenum, Aspergillus terreus and A. fumigatus) was studied. The fungi under study differed significantly in the degree of production of cellulases and xylanase. A. fumigatus was a poor producer of ,aglucosidase. P. purpurogenum was efficient producer of xylanase. No correlation could be observed between growth and production of different enzymes.